Effect of joint mobilization, strengthening and stretching programme of ankle on balance in elderly - Choudhary, Nikhil; Mohd Dar, Shahid (Indian Academy of Geriatrics, 2011)
Objective: To find out the effect of strength training of dorsiflexors of ankle on the balance in elderly. Methods: Healthy elderly were selected and divided into two groups. One group got stretching, mobilization and strength training of ankle dorsiflexors while no exercises were given to the other group. Balance of the two groups were compared by means of functional reach test and performance oriented mobility assessment. Results: A significant improvement in the balance was found in the exercise group. Conclusion: By restoring the normal biomechanics and increased dorsiflexors strength of the ankle, there is improvement in balance in elderly. Keywords: falls, balance, ankle range of motion, elderly. (Journal of The Indian Academy of Geriatrics, 2011; 7: 150-153